Bureaucracy, overload, and management: The determinants of teacher burnout - Sara TORRE; Claudio LEONE; Pietro CRESCENZO; Maria Beatrice LIGORIO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Background:While burnout in teachers is frequently studied in relation to personal resources and individual obstacles, less attention has been given to social and systemic stressors. This study investigates how various interpersonal, group, and community-related factors contribute to the development of burnout symptoms in the teaching profession. Methods: A quantitative design was adopted to explore the impact of 11 identified stressors on teacher burnout. A sample of 274 Italian teachers (84.67% female; mean teaching experience = 17.99 years, SD = 10.21) completed a survey assessing stress levels and the Maslach Burnout Inventory – General Survey (MBI-GS). The analysis focused on three dimensions of burnout: emotional exhaustion, cynicism, and reduced professional efficacy. Results: The findings revealed complex cause-effect relationships. Bureaucratic obligations, overlapping stressors, difficulties in classroom management, and challenges during lesson delivery emerged as the most significant predictors of the burnout subdimensions. Conclusions: The results highlight the importance of adopting a systemic and social perspective in the analysis of teacher burnout. A more comprehensive framework is needed to fully understand the multifactorial nature of stress in the teaching profession and to develop effective intervention strategies.